Post-Activation Performance Enhancement: Save Time With Active Intra-Complex Recovery Intervals - Trybulski, Robert; Makar, Piotr; Alexe, Dan Iulian; Stanciu, Silvius; Piwowar, Rafał; Wilk, Michal; Krzysztofik, Michal (Frontiers in Physiology, 2022)
This study aimed to determine whether the intra-complex active recovery within the strength-power potentiating complex will impact the upper-body post-activation performance enhancement effect and how the magnitude of this effect will change across the upper-body complex training session. Thirteen resistance-trained males (age, body mass, height; experience in resistance training, one-repetition maximum in bench press were: 27 ± 4 yr; 92.3 ± 15.4 kg; 182 ± 6 cm; 6.4 ± 2.4 yr, 118 ± 29 kg, respectively) participated in this study. Each participant completed a baseline bench press throw performance assessment at 30% 1RM. Next, five strength-power potentiating complexes consisting of a bench press at 80% 1RM until the average barbell velocity decreased by 10% as a conditioning activity and 6 minutes later, re-test of bench press throw. During one experimental session during rest-interval inside the complex, they performed swiss ball leg curls, while between the complexes, a plank exercise (PAP-A). During the second experimental session, participants performed no exercises within the strength-power potentiating complex and between them (PAP). Under control conditions, participants ran the same protocol (as PAP condition) without the CA (CTRL). Friedman’s test showed significant differences in Peak (test = 90.634; p < 0.0001; Kendall’s W = 0.410), Average (test = 74.172; p < 0.0001; Kendall’s W = 0.336) Barbell Velocity during bench press throw. Pairwise comparisons indicated that Peak and Average Barbell Velocity significantly increased in 4th set [p = 0.022; effect size (ES) = 0.76; p = 0.013, ES = 0.69; respectively], and the Average Barbell Velocity was also increased in 2nd set (p = 0.018; ES = 0.77) in comparison to baseline value during PAP-A condition. Moreover, the Peak Barbell Velocity was increased in 2nd (p = 0.008; ES = 0.72) and 3rd (p = 0.019; ES = 0.76) set compared to the baseline value during PAP condition. This study showed that body-weight lower-body exercise as an intra-complex active recovery did not impair the upper-body post-activation performance enhancement effect across the complex training session.